Parameterized complexity of configuration integer programs - Knop, Dušan; Koutecký, Martin; Levin, Asaf; Mnich, Matthias; Onn, Shmuel (Operations research letters, 2021)
Configuration integer programs (IP) have been key in the design of algorithms for NP-hard high-multiplicity problems. First, we develop fast exact (exponential-time) algorithms for Configuration IP and matching hardness results. Second, we showcase the implications of these results to bin-packing and facility-location-like problems.